Off-lattice protein structure prediction on 3D hydrophobic-polar side-chain model using parallel simulated annealing - Campanano, Gerald Roy D.; Lopez, Francis Jonathan J.; Ventura, Rowel D. (College of Engineering, University of the Philippines Diliman, 2016)
Proteins can perform different functions in living organisms such as transporting molecules and DNA replication. These functions are closely related to the conformations of amino acids chains that make each protein. Unfortunately, finding the final conformation or folded structure of a protein given its amino acid sequence is proven to be NP-Complete. Different models have been made to better understand the protein folding problem wherein the HP model is the most popular. A variation of the HP model which includes side-chain representation is also being used but often implemented only on lattices. In this paper, an off-lattice implementation of the HPSC model in 3D space is presented and a metaheuristic method called simulated annealing is used to find a good confrontation of a given protein. The total energy values and the number of hydrogen bonds formed will be compared to previous researches. Lastly, parallel computing will be applied to the method for improved identification of final conformations.